(untitled) ([Inter]sections, 2025)
Often set in the mythical landscapes of the American West, the American road narrative conveys the promise of spatial and social mobility that characterize the American Dream and that are made possible by going on the road. Nevertheless, this idea of mobility has been reserved to traditional road heroes—white, heteronormative men—and systemically excluded minorities from accessing the road in the same terms. Consequently, this had an impact on how American road narratives written by and about minorities have been received and analyzed. This article aims to analyze the novel Lost Children Archive (2019), written by Mexican-American author Valeria Luiselli, therefore applying a transnational perspective to the American road narrative genre. Drawing on Ann Brigham’s concept of incorporation, it aims to understand how this narrative is positioned in the matrix of the genre and how it is able to deconstruct the hegemonic discourses that shape it.